PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SDN 16 AIR TAWAR TIMUR - Azizah, Wafiq; Arwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by field observations indicating that students’ learning outcomes had not yet been maximized due to the lack of learning activities that actively involved students. This condition occurred because the learning process was still teacher-centered, resulting in low levels of student participation during classroom instruction. The objective of this research was to describe the improvement in students’ learning outcomes in Pancasila Education through the implementation of the Problem Based Learning (PBL) model in Grade IV of SDN 16 Air Tawar Timur. This research employed Classroom Action Research (CAR) using both qualitative and quantitative approaches. The research was conducted in two cycles, following procedures that included planning, implementation, observation, and reflection. The data collected were related to learning outcomes resulting from the implementation of the Problem Based Learning model. Data collection techniques included observation analysis, tests, and non-test instruments. The research subjects consisted of the classroom teacher as an observer, the researcher as the practitioner or teacher, and 27 fourth-grade students of SDN 16 Air Tawar Timur. The research findings showed the following results. First, the teaching module in Cycle I achieved an average score of 89.6% (Good), which increased to 95.8% (Very Good) in Cycle II. Second, the implementation of learning from the teacher aspect in Cycle I obtained an average of 87.4% (Good), which increased to 96.4% (Very Good) in Cycle II. Third, the implementation of learning from the student aspect in Cycle I reached an average of 89.2% (Good), which increased to 96.4% (Very Good) in Cycle II. Fourth, students’ learning outcomes in Cycle I obtained an average score of 78.8 (Fair), which increased to 94.3 (Very Good) in Cycle II. Therefore, it can be concluded that the Problem Based Learning model can improve students’ learning outcomes in Pancasila Education in Grade IV of SDN 16 Air Tawar Timur.